Survey measuring Viet Nam sustainable development goal indicators on children and women Survey findings report December 2021 (Hong Duc, 2022)
The General Statistics Office of Viet Nam and the United Nations Children's Fund (UNICEF) Viet Nam Country Office are happy to release the findings from the Survey measuring Viet Nam Sustainable Development Goal indicators on Children and Women (SDGCW) 2020-2021. The Viet Nam SDGCW survey was carried out in 2020-2021 by General Statistics office (GSO) of Viet Nam in collaboration with government ministries as part of the Global MICS programme of UNICEF. Technical and finnacial support was provided by the UNICEF and UNFPA.